Structural and Dielectric Properties of Zn1-x-yCdxLiyO Solid Solution - Kamruzzaman, M; Khan, MKR; Rahman, MM; Shahjahan, M; Karal, MAS (Journal of Bangladesh Academy of Sciences, 2009)
Zn1-x-yCdxLiyO (x=0.30 and y=0.05, 0.10, 0.15, 0.20) have been prepared by solid state reaction method. The prepared samples have been characterized by structural and dielectric measurements. X-ray diffraction (XRD) patterns show a good crystalline nature having double crystal structure and indicates the phase mixing of the constituent components. The hexagonal phase corresponding to ZnO and cubic phase to CdO is well defined and the lattice parameters are consistent with the published values (Grant in Aid report 1987). The estimated lattice parameters, bond length and crystallite size are quite consistent corresponding to the hexagonal ZnO and cubic CdO which suggests the formation of super lattice structure of the system. Crystallite size at different crystallographic planes analyzed from XRD for both ZnO and CdO lie between (15-50) nm. The variation of the dielectric constant of the samples with frequency is systematic and the dielectric constant increases with the increase of Li in the solution. doi: 10.3329/jbas.v32i2.2430 Journal of Bangladesh Academy of Sciences Vol.32(2) 2008 234-242